Strategy of Improvement Domestic Products in Government Goods/Services Procurement in Bogor Regency - Hidayat, Aldiansyah Iqbal; Silitonga, Mala Sondang (Yayasan Riset dan Pengembangan Intelektual, 2025)
This study explores strategic approaches to enhancing the utilization of domestic products (Produk Dalam Negeri, PDN) in public procurement processes within Bogor Regency, Indonesia. Anchored in the national policy framework promoting local industrial development and economic resilience, the research investigates institutional, regulatory, and procedural barriers that impede optimal implementation of PDN mandates at the regional level. Employing a qualitative descriptive methodology, the study draws on interviews with government procurement officials and local vendors, as well as an analysis of procurement plans, budget realization data, and policy documents. Findings reveal that the underperformance in PDN absorption is primarily attributed to the absence of localized regulatory instruments, inadequate integration of PDN priorities in regional planning and performance systems, limited institutional capacity, and fragmented coordination among key stakeholders. Furthermore, systemic weaknesses in procurement planning and vendor engagement hinder compliance with national targets, resulting in substantial gaps between planned and realized domestic product spending. To address these issues, the study offers a set of comprehensive recommendations. Practically, it advocates for the formulation of local regulations and technical guidelines, capacity building for procurement actors, and the development of digital procurement platforms prioritizing domestic suppliers. From a policy perspective, it recommends the institutionalization of performance-based monitoring and evaluation systems, inter-agency coordination mechanisms, and incentive structures. Theoretically, the research contributes to the discourse on sustainable procurement by proposing a framework linking institutional readiness, procurement processes, and local economic impact. The study concludes that with targeted regulatory reforms, institutional strengthening, and strategic alignment between national mandates and local practices, Bogor Regency can significantly improve its PDN realization, thereby reinforcing local industry participation in public sector supply chains and advancing sustainable regional development.